Ensino médio em tempo integral: a política nacional do novo Ensino médio e sua gestão no estado do Amapá (2016-2019) - FONSÊCA, Kátia de Nazaré Santos (UNIFAP – Universidade Federal do Amapá, 2022)
This research deals about the execution of the National Full time High School Policy by the Government of the State of Amapá. The problem asks: With the accession of the State Government to the Policy for the Promotion of FTHS, resulting from Law 13.415/2017, what are the consequences for the state education system? The axis of this research articulates elements of implantation and implementation of the current standard stipulated to the HS, highlighting the conditions that this policy is realized and to what extent it contributes to the achievement of Goal 6 of the State Education Plan/AP. The objectives are to evaluate the modus operandi of the GEA in the materialization of the High School Reform and related the complications; identify the administrative, pedagogical and physical structural measures taken by SEED to implement the FTHS; and check the degree of relationship between the partial results of the execution of the FTHS and the economic and financial planning of SEED for this expansion in full time. The investigation, inspired by Dialectical Historic Materialism, uses the studies of researchers in the Public Policies area, notably those related to the educational area, like: Saviani, Dermeval; Behring, Elaine; Shiroma, Eneida; Frigotto, Gaudencio; Souza, Gilberto; Giolo, Jaime; Moll, Jaqueline; Evangelista, Olinda; etc, and from them collects the theoretical-methodological references that support the analysis and criticisms developed in the corpus of the work. The methodology articulates field and documentary research. In the field, a visit was made at SEED and at two FTHS located in Macapá, to capture political, pedagogical and financial factors determining the modeling of the new High School. Semi structured interviews were used to collect data from the reporting subjects - managers of the macro and micro educational systems in Amapá involved in this policy, in addition to members of the technical pedagogical staff and teachers of the FTHS. About the documentary research, the investigation fell on the legislative corpus guiding the High School Reform, as well as on documents prepared by private devices of hegemony, essential elements for understanding the real interests and movements that the agents of power have been carrying out around Brazilian education. The results indicate that the Law 13.415/2017 established, in record time, a profound reconfiguration of the HS, without guaranteeing to the state education system the necessary contribution to the reorganization and operability - with quality - of this educational segment in the full-time regime. Concludes that the new archetype applied to high school in Amapá, due to the default of financial resources, has been compromising the execution of the expected Pedagogical Model, as well as the permanence of students in school, resulting in serious risks of making the link between GEA and the Federal Program for the Promotion of Full Time Schools, even though it may partially achieve PEE Goal 6 within the established deadline, in addition to reinforcing the lame scenario in which Brazilian high school is.